Secrecy and insurgency : socialities and knowledge practices in Guatemala - Posocco, Silvia (University Alabama Press, 2014)
"Secrecy and Insurgency deals with the experiences of guerrilla combatants of the Fuerzas Armadas Rebeldes (Rebel Armed Forces) in the aftermath of the peace accords signed in December 1996 between the Guatemalan government and guerrilla insurgents. Drawing on a broad field of contemporary theory, Silvia Posocco's Secrecy and Insurgency presents a vivid ethnographic account of secrecy as both sociality and a set of knowledge practices. Informed by multi-sited anthropological fieldwork among displaced communities with experiences of militancy in the guerrilla organization Fuerzas Armadas Rebeldes, the book traces the contours of dispersed and intermittent guerrilla social relations, unraveling the gendered dimensions of guerrilla socialities and subjectivities in a local context marked by violence and rapid social change. The chapters chart shifting regimes of governance in the northern departamento of Peten; the inception of violence and insurgency; guerrilla practices of naming and secret relations; moral orders based on sameness and sharing; and forms of relatedness, embodiment, and subjectivity among the combatants. The volume develops new critical idioms for grappling with partiality, perspective, and incompleteness in ethnography and contributes to new thinking on the anthropology of Guatemala. Secrecy and Insurgency will be of interest to social and cultural anthropologists, human geographers, and those interested in Latin American studies, human rights, women's studies, and gender studies"--